PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 184 PEKANBARU - Lestari, Leila; Daud, Damanhuri; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstrakThe purpose of this research is to improve learning achievement in natural science on fourth grade students at SDN 184 Pekanbaru on academic year 2011/2012 through “the application of jigsaw type cooperative learning’. This research was conducted from April until May 2012. Subject of the research is fourth grade students SDN 184 pekanbaru, which contain forty students. There are 19 boys and 21 girls. Type of the research is collaborative classroom action research (teacher works with Researcher). This research contains two cycles. Each cycle consists of 4 meeting. Parameter of this research is student’s achievement after action for each cycle (first and second daily test). Instruments of the research contain learning tools (syllabus, RPP, LKS, learning result paper sheet), students and teacher observation sheet. Data will be analyzed descriptively. Average of students learning achievement increased in which the begining students score of students was 40,00 (very poor). It improved into 77,50 (good) in first daily test. In second daily test the score increased to 92,50 (very good). Improvement score from base score to first cycle is 22,50 whereas from first cycle to second cycle is 7,50. Total improvement score is 30,00. Average of student activity in first cycle is 66,06% (good). And it improved to 89,28% (very good) in second cycle. Average of teacher activity in first cycle is 70,83% (good). And it was improved to 91,06% (very good) in second cycle. Based on the data, researcher concludes the application of jigsaw type cooperative learning can improve learning achievement in natural science on Fourth grade students at SDN 184 Pekanbaru.Keyword: jigsaw type cooperative learning, learning achievement of natural science .